2016
DOI: 10.1111/bor.12192
|View full text |Cite
|
Sign up to set email alerts
|

An anisotropy of magnetic susceptibility (AMS) fabric record of till kinematics within a Late Weichselian low Baltic till, southern Sweden

Abstract: Herein we report on the results of an anisotropy of magnetic susceptibility (AMS) fabric case‐study of two Late Weichselian tills exposed in a bedrock quarry in Dalby, Skåne, southern Sweden. The region possesses a complex glacial history, reflecting alternating and interacting advances of the main body of the Scandinavian Ice Sheet (SIS) and its ice lobes from the Baltic basin, perhaps driven by streaming ice. AMS till fabrics are robust indicators of ice‐flow history and till kinematics, and provide a unique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
(111 reference statements)
0
2
0
Order By: Relevance
“…The second responsible mineral may be titanomagnetite, which is popular in crystalline rocks included in the studied tills. A third mineral may be maghemite, which Hopkins et al (2016) suggested may account for the marked decrease in magnetization at 200-300°C. Maghemite has been identified in sediments formed in cold environments (Kodama, 1982), including glacial tills (Gentoso et al, 2012).…”
Section: Magnetization Carriersmentioning
confidence: 99%
See 1 more Smart Citation
“…The second responsible mineral may be titanomagnetite, which is popular in crystalline rocks included in the studied tills. A third mineral may be maghemite, which Hopkins et al (2016) suggested may account for the marked decrease in magnetization at 200-300°C. Maghemite has been identified in sediments formed in cold environments (Kodama, 1982), including glacial tills (Gentoso et al, 2012).…”
Section: Magnetization Carriersmentioning
confidence: 99%
“…An effective tool for measuring the average orientation of fine grains is the anisotropy of magnetic susceptibility (AMS) method, which has been used to determine not only the directions of movement, but also the mechanism of ice-sheet movement, and to reconstruct processes of subglacial till formation. This method of studying tills has been refined across more than six decades of use (e.g., Fuller, 1962; Stupavsky and Gravenor, 1975; Stewart et al, 1988; Hooyer et al, 2008; Thomason and Iverson, 2009; Gentoso et al, 2012; Fleming et al, 2013; Tylmann et al, 2013; Ankerstjerne et al, 2015; Król and Wachecka-Kotkowska, 2015; Hopkins et al 2016; McCracken et al, 2016; Narloch et al, 2021; Teodorski et al, 2021).…”
Section: Introductionmentioning
confidence: 99%